2006
DOI: 10.1002/jbt.20145
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of chlorpyrifos and chlorpyrifos oxon by human hepatocytes*

Abstract: The metabolism of chlorpyrifos (CPS) and chlorpyrifos oxon (CPO) by human hepatocytes and human liver S9 fractions was investigated using LC-MS/MS. Cytochrome P450 (CYP)-dependent and phase II-related products were determined following incubation with CPS and CPO. CYP-related products, 3,5,6-trichloro-2-pyridinol (TCP), diethyl thiophosphate, and dealkylated CPS, were found following CPS treatment and dealkylated CPO following CPO treatment. Diethyl phosphate was not identified because of its high polarity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 25 publications
(42 reference statements)
2
29
0
Order By: Relevance
“…During the first 72 h following exposure, approximately 30% of the urinary TCPy was present as free TCPy, whereas after 96 h, less than 10% was free, suggesting that either the rate of glucuronide conjugation of TCPy is slow, and/or that glucuronidation capacity was saturated at relatively high substrate concentration. Choi et al (2006) also identified the O-glucuronides of both TCPy and DCPy following incubation of human hepatocytes with chlorpyrifos. Interestingly, they also identified an S-glucuronide conjugate of chlorpyrifos, which they proposed was the result of secondary displacement of 2-aminopropanoic acid from the chlorpyrifos-cysteine conjugate that was derived from the chlorpyrifos-glutathione conjugate.…”
Section: Effects Of Induction and Inhibition Of Cyps On The Metabolismentioning
confidence: 93%
See 3 more Smart Citations
“…During the first 72 h following exposure, approximately 30% of the urinary TCPy was present as free TCPy, whereas after 96 h, less than 10% was free, suggesting that either the rate of glucuronide conjugation of TCPy is slow, and/or that glucuronidation capacity was saturated at relatively high substrate concentration. Choi et al (2006) also identified the O-glucuronides of both TCPy and DCPy following incubation of human hepatocytes with chlorpyrifos. Interestingly, they also identified an S-glucuronide conjugate of chlorpyrifos, which they proposed was the result of secondary displacement of 2-aminopropanoic acid from the chlorpyrifos-cysteine conjugate that was derived from the chlorpyrifos-glutathione conjugate.…”
Section: Effects Of Induction and Inhibition Of Cyps On The Metabolismentioning
confidence: 93%
“…These would shift the balance toward detoxication even further. Studies in rats (Sultatos et al, 1984) and humans (Choi et al, 2006) have indeed indicated that chlorpyrifos oxon does not escape the liver, confirming that the active metabolite, once formed, is readily detoxified. Extrahepatic sites of activation and detoxication (with the exception of plasma PON1 and carboxylesterases) have not been studied to a great extent, and should be further investigated.…”
Section: Iic6 Balance Of Activation and Detoxication Pathwaysmentioning
confidence: 93%
See 2 more Smart Citations
“…Organophosphorus insecticides, like chlorpyrifos (CPF) and chlorpyrifos-methyl (CPFm), were a large class of toxic chemical compounds that have been widely used in the agriculture production and home application (Jiang et al, 2008;Singh and Walker, 2006;Choi et al, 2006). In recent years there has been increasing attention given to the accidents linked to organophosphorus insecticides (Caldas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%